Impact of fibre moisture content on the structure/mechanical properties relationships of PHBV/wheat straw fibres biocomposites - Berthet, M.-A.; Gontard, N.; Angellier-Coussy, H. (Composites science and technology, 2015)
The objective of the present work was to investigate the impact of fibre moisture, at the moment of the manufacturing process, on the relationships between the structure of PHBV/wheat straw fibres composites and their final mechanical properties, with a focus on the interphase role. For that purpose, wheat straw fibres were equilibrated at extreme relative humidity conditions before extrusion with PHBV, reaching moisture contents of 2 wt% w.b. and 14.2 ± 0.4 wt% w.b. at 0 and 98% RH, respectively. The structure and mechanical properties of resulting composites (prepared with a fibre content of 20 wt%) were compared to those of materials filled with fibres classically dried (moisture content of 3 wt% w.b.). It was shown that the fibre/matrix adhesion was visually not affected by the initial fibre moisture content. However, PHBV molecular weight decreased significantly with increasing fibre moisture content, which was attributed to hydrolysis reactions induced by residual water molecules. The increase in crystallinity along with initial fibre moisture content was put in relation to the observed decrease of molecular weight. In spite of structural differences, the tensile properties were similar for all composites, leading to the conclusion that the initial fibre moisture content was not a predominant factor for controlling the mechanical properties of PHBV/wheat straw fibres composites.